The effect of remittance outflow towards economic growth in Malaysia - Rahimah Razali; Caroline Geetha Arokiadasan; Roslinah Mahmud (SAS Publishers, 2016)
This study aimed to discuss the short run and long run relationship between remittance outflow and economic growth in Malaysia from 1982 until 2014. Annual data was used where the dependent variable was economic growth and the independent variables were remittance outflow, export, exchange rate, FDI outflow and labor force. Johansen Co- integration was used to estimate the long run relationship meanwhile VECM was used to estimate the short run relationship between the variables. The findings revealed that there are long run relationship between remittance outflow, exchange rate, export, and FDI inflow and labor force to economic growth. Meanwhile, in short run, remittance outflow, export, and labor force influenced GDP. Remittance outflow was positively significant in the short and long run. This could be due to the use of foreign labor to produce goods and services in the country. The goods and services produced by the foreigners helped to boost the production process in the country. This encourages export of goods and services which eventually enhances the purchasing power of the nation. As export increases, GDP of the nation also increases resulting in a positively significant impact with the remittance outflow. Additionally, foreign direct investment inflow had insignificant impact in short run towards economic growth because of its low total factor productivity rate. As for the exchange rate, Malaysia was practicing a managed exchange rate system that was constantly exposed to shocks. It needs the interference of the government to have a positive impact towards economic growth